2017
DOI: 10.1080/15384101.2017.1304339
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the BmCyclin L1-BmCDK11A/B complex in relation to cell cycle regulation

Abstract: Cyclin proteins are the key regulatory and activity partner of cyclin-dependent kinases (CDKs), which play pivotal regulatory roles in cell cycle progression. In the present study, we identified a Cyclin L1 and 2 CDK11 2 CDK11 splice variants, CDK11A and CDK11B, from silkworm, Bombyx mori. We determined that both Cyclin L1 and CDK11A/B are nuclear proteins, and further investigations were conducted to elucidate their spatiofunctional features. Cyclin L1 forms a complex with CDK11A/B and were co-localized to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Consistently, previously studies have reported the tumor-promoting anti-cancer effects of CDK11A (30,31). Liu and colleagues also found that CDK11A upregulation suppresses cellular proliferation by inducing cell cycle arrest (32).…”
Section: Discussionsupporting
confidence: 80%
“…Consistently, previously studies have reported the tumor-promoting anti-cancer effects of CDK11A (30,31). Liu and colleagues also found that CDK11A upregulation suppresses cellular proliferation by inducing cell cycle arrest (32).…”
Section: Discussionsupporting
confidence: 80%
“…Cytosolic phospholipase has been verified to function in the synthesis of prostanoid involved in ovarian development in Penaeus monodon 30 . In addition, prediction results showed that many target genes participate in gonadal development, such as cyclin L1, HSP, and zinc finger protein 3133 . For instance, Hsp110 is required for progression of spermatogenesis, and is associated with germ cell apoptosis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, blocking CDK11 and/or Cyclin L1 expression using siRNAs arrested these cells in G2/M, with decreased G1 phase cells. Both overexpression and inhibited expression of CDK11 and/or Cyclin L1 reduced the viability of these cells, suggesting a window of appropriate CDK11 levels in these non-cancer cells [57]. The effects of CDK11 loss in silkworm cells align with similar effects during mouse embryo development [15].…”
Section: Discussionmentioning
confidence: 99%